Pembelajaran Pidato di Era Multiliterasi Digital - Kartadireja, Welly Nores; Sastromiharjo, Andoyo; Lisnawati, Iis (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to understand the impact of technology integration in the digital multiliteracy era on the strategies, processes, and outcomes of speech learning in the Department of Indonesian Language Education, FKIP, Siliwangi University. The method used is a qualitative case study with purposive sampling technique. Data were obtained through observation, in-depth interviews, and document analysis. Data analysis was carried out interactively through reduction, presentation, and conclusion drawing.The results showed that the application of digital technology significantly improved speech learning strategies. Students become more active, creative, and communicative in composing and delivering speeches through online platforms. Students' digital literacy increased, marked by the ability to understand digital content, adapt speeches to audiences, and utilize online media. Lecturers also find it easy to be flexible, provide feedback, and utilize digital resources. Digital multiliteracies proved effective in supporting the development of speech learning in higher education. Abstrak Penelitian ini bertujuan untuk memahami dampak integrasi teknologi di era multiliterasi digital terhadap strategi, proses, dan hasil pembelajaran pidato di Jurusan Pendidikan Bahasa Indonesia FKIP Universitas Siliwangi. Metode yang digunakan adalah studi kasus kualitatif dengan teknik purposive sampling. Data diperoleh melalui observasi, wawancara mendalam, dan analisis dokumen. Analisis data dilakukan secara interaktif melalui reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan teknologi digital secara signifikan meningkatkan strategi pembelajaran pidato. Mahasiswa menjadi lebih aktif, kreatif, dan komunikatif dalam menyusun serta menyampaikan pidato melalui platform online. Literasi digital mahasiswa meningkat, ditandai dengan kemampuan memahami konten digital, menyesuaikan pidato dengan audiens, dan memanfaatkan media daring. Dosen juga merasakan kemudahan dalam fleksibilitas, pemberian umpan balik, dan pemanfaatan sumber daya digital. Multiliterasi digital terbukti efektif mendukung pengembangan pembelajaran pidato di perguruan tinggi.